Graphene oxide modulates dendritic cell ability to promote T cell activation and cytokine production. Issue 46 (14th November 2022) - Parker, Helen; Gravagnuolo, Alfredo Maria; Vranic, Sandra; Crica, Livia Elena; Newman, Leon; Carnell, Oliver; Bussy, Cyrill; Dookie, Rebecca S.; Prestat, Eric; Haigh, Sarah J.; Lozano, Neus; Kostarelos, Kostas; et al.
Abstract : sGO–OVA nanocomplexes increase uptake of OVA protein by dendritic cells, enhancing their ability to induce CD4 + T cell granzyme B secretion and Foxp3 expression. Abstract : An important aspect of immunotherapy is the ability of dendritic cells (DCs) to prime T cell immunity, an approach that has yielded promising results in some early phase clinical trials. However, novel approaches are required to improve DC therapeutic efficacy by enhancing their uptake of, and activation by, disease relevant antigens. The carbon nano-material graphene oxide (GO) may provide a unique way to deliver antigen to innate immune cells and modify their ability to initiate effective adaptive immune responses. We have assessed whether GO of various lateral sizes affects DC activation and function in vitro and in vivo, including their ability to take up, process and present the well-defined model antigen ovalbumin (OVA). We have found that GO flakes are internalised by DCs, while having minimal effect on their viability, activation phenotype or cytokine production. Although adsorption of OVA protein to either small or large GO flakes promoted its uptake into DCs, large GO interfered with OVA processing. In terms of modulation of DC function, delivery of OVA via small GO flakes significantly enhanced DC ability to induce proliferation of OVA-specific CD4 + T cells, promoting granzyme B secretion in vitro . On the other hand, delivery of OVA via large GO flakes augmented DC ability to induce proliferation of OVA-specific CD8 + T cells, and their production of IFN-γ and granzyme B. Together, these data demonstrate the capacity of GO of different lateral dimensions to act as a promising delivery platform for DC modulation of distinct facets of the adaptive immune response, information that could be exploited for future development of targeted immunotherapies.